Biohydrogen production from sago hampas by Clostridium butyricum A1 - Jenol, Mohd Azwan (2014)
The hydrogen has been applied in fuel cell vehicle and expected to shift toward the technologies that produce no net greenhouse gas effects. Biohydrogen production from biomass is now attracting many researchers in developing a renewable, clean and environmental friendly biofuel. The availability of abundant biomass from various sources could possibly be an advantage for the production of biohydrogen as a competitive energy carrier in the future. There are vast choices of possible types of biomass that can be subjected as the carbon source for the production of biohydrogen including starch based and lignocellulosic biomass. Sago industry is one of the possible source of biomass since the industry is producing large quantities of starch and lignocellulosic biomass. Statistically, a single sago starch processing mill has produced 7 ton/day of sago hampas. Thus, this study aimed to produce biohydrogen from sago biomass by locally isolated biohydrogen producer and to optimize the production of biohydrogen using statistical approach. The locally isolated biohydrogen producer Clostridium butyricum A1 was successfully isolated from landfill soil. This strain produced a biohydrogen yield of 1.90 mol H2/mol glucose with productivity of 170 mL/L/h using pure glucose as substrate. The highest cumulative biohydrogen collected after 24 h of fermentation time was 2468 mL/Lmedium. Biohydrogen fermentation using sago hampas hydrolysate generate higher biohydrogen yield (2.65 mol H2/mol glucose) compared to sago pith residue (SPR) hydrolysate at 2.23 mol H2/mol glucose. A higher biohydrogen productivity of 1757 mL/L/h was obtained when using sago hampas hydrolysate much higher when compared to pure glucose at 170 mL/L/h. In this study, the new isolate C. butyricum A1 together with the use of sago biomass as the substrate is a promising technology for future biohydrogen production. Optimization of biohydrogen production from sago hampas hydrolysate by C. butyricum A1 was conducted using four variables including temperature, sugar concentration, initial pH and inoculum size. This study has applied central composite design (CCD) and artificial neural network (ANN) as the optimization step. As a result, three out of four variables have given significant effects on the production of biohydrogen from sago hampas hydrolysate; which are temperature, sugar concentration and pH. Using ANN, pH was found to be the most significant variable with the relative importance of 73.6%. The optimum conditions given by ANN with respect to optimized biohydrogen yield of 2.92 mol of H2/mol of glucose are 39°C, pH 8, initial glucose concentration at 13 g/L and 13% (v/v) inoculum size. As conclusions,biohydrogen production from sago hampas by C. butyricum A1 has successfully conducted and optimized.